A numerical study of damage mechanisms in the CAI of laminated composites for aerospace applications - Yang, Yu (2016)
Compression after impact (CAI) is one of the crucial factors affecting material selection and determination of allowable design values in aircraft design process for fibre reinforced composite laminates. The major objectives of this thesis are to investigate the damage mechanismof CAI and to obtain a practical prediction method accordingly. Through literature review, it has been found that current perceptions of CAI damage mechanism are too categorical as they conceive either of two possible failure modes only, delamination propagation and in-plane compressive failure due to stress concentration. A finite element (FE) modelling method has been presented, which takes both potential failure modes into account simultaneously. Through a substantial parametric study employing this FE modelling method, it has been found that these two failure modes co-exist in the damage process, and compete to be the dominant failure mode favoured by various factors,among which the delamination multiplicity is one of the major factors dictating the damage mechanism. Further investigation has been carried out with more realistic FE models of CAI, which take all major damage modes due to impact into account, such as delamination distribution, transverse matrix cracks and fibre breakage. Especially, a method of determining the delamination distribution over laminate thickness direction based on the result of double-sided ultrasonic scanhas been presented, which has been extremely helpful to preserve the key features of delamination distribution in corresponding FE models. Through the investigation, the damage mechanism of CAI has been concluded as in-plane failure due to stress concentration at delamination front and large extent of delamination propagation is unlikely to take place during the loading process. This conclusion is fully justified for material systems with toughened matrix as employed in aerospace widelynowadays. In the meantime, a practical strategy of applying the CAI prediction method employing this FE modelling is presented, which overcomes the deficiency of other similar methods that require extremely refined and often unaffordable mesh as for the FE modelling. Based on the conclusion of CAI damage mechanism obtained above, a simplified CAI prediction method has been presented, which takes advantage of the results from ultrasonic scan. It is computationally efficient, numerically accurate and physically sound. In order to investigate the degrading tendency of stiffness over the delaminated area, an improved inverse method has been developed, through which it has been found that the stiffness degradation is neither uniform over the delaminated area nor constant during compression process in CAI cases. In addition, adeficiency of cohesive element has been spotted. It roots from the discrepancy of coordinate systems of cohesive elements and crack propagation direction, and may bring additional numerical error if used improperly. All the outcomes of this project, modelling strategies and prediction methods as presented in this thesis are highly valuable in CAI evaluationfrom experimental, theoretical and practical perspectives. After further validation, they should be applicable to most CAI cases faced in the aerospace industry currently.